Assessing One for one and none for all – The Radical Right in the European Parliament - Matthias Diermeier; Hannah Frohwein; Aljoscha Nau (London School of Economics and Political Science (LSE), European Institute, 2021)
The radical right in Europe seemed to be on an unprecedented rise. In the run-up to the European Parliament elections in 2019, a newly founded 'super-faction' profoundly scared established politicians. In contrast to the widespread fear of a consolidated right-wing, this contribution carves out that the radical right' policy congruence in the European Parliament is limited due to internal division primarily caused by the parties' nativist core ideology. Splitting the radical right into its Eastern and Western European offshoots, reveals a significant economic nativism that systemically prevents comprehensive interregional cooperation. What is more, despite common authoritarian grounds with foreign powers such as the Peoples Republic of China and Russia and their significant advance on influencing the European radical right, nativism divides the radical right also in their stance on foreign autocracies. Whereas economic nativism triggers an opposition against China within the Western European radical right, political nativism in the East obviates cooperation between European rightwingers regarding Russia.
Keywords: 330; radical right; authoritarianism; nativism; economic policy; European Parliament